Environmental Hygiene and Sanitation Practices Against TB Incidents in the Work Area of Kesamben Health Center, Blitar Regency - Lukman Ali Widyantara; Ratna Wardani (Universitas STRADA Indonesia, 2021)
Tuberculosis is an infectious disease caused by Mycrobacterium Tuberculosis. Indonesia is ranked 3rd largest burden of tuberculosis in the world (8%) after India (27%) and China (9%). The increase in the number of cases in Indonesia continues to increase every year. Although many prevention and management efforts, the spread of tuberculosis bacteria is very easy to spread. This study aims to determine the relationship between hygiene practices and environmental sanitation to the incidence of tuberculosis in the Kesamben Health Center Work Area, Blitar Regency. This study is a quantitative study with a survey design and analytical observation with a retrospective approach (case control). The population of this study was the community in the Kesamben Health Center work area using purposive sampling techniques and 40 respondents were found. Data collection using questionnaires and observation sheets, analyzed using SPSS with Logistic Regression Test with α = 0.05. The results of the statistical test showed that there was a relationship between hygiene practices and the incidence of tuberculosis with a sig value. 0.005 and there is no relationship between environmental sanitation and TB incidence with a sig. value of 0.121. This is because the habit of implementing cleanliness is not practiced, especially the use of masks which are considered to interfere with breathing when doing activities such as working and other activities. It is hoped that further research can develop research related to TB incidence using other variables such as health services, knowledge, PMO and more variables.